Wsparcie szkół w edukacji włączającej = Support for schools in inclusive education - Dwojakowska, Weronika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the theory and role of inclusive education in the context of school functioning, discussing its theoretical foundations. It illustrates the role and activities of a consulting teacher by analyzing the difficulties and needs reported by teachers in implementing inclusive education. It also highlights the growing number of special education needs statements and the insufficient preparation of teaching staff to work in educational institutions. The central focus is the presentation of a support model for educational institutions, implemented at the School and Preschool Complex in Bierzwnik during the 2023/2024 school year. This model is based on a needs assessment and a cycle of activities including specific workshops, training sessions, and consultations for teachers and school leadership. Evaluation following the implementation of the model shows an increase in teachers? competencies and a reduction in resistance to working with students with special educational needs.
Keywords: edukacja włączająca; placówki edukacyjne; dziecko z niepełnosprawnością; nauczyciele; wsparcie; inclusive education; educational institutions; child with a disability; teachers; support